PENGARUH GRID PEJARAK DAN NOZZLE TERHADAP PARAMETER TERMOHIDROLIKA PERANGKAT BAHAN BAKAR REAKTOR AP1000 - Isnaini, Muhammad Darwis (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
One of the spacer grids function was to increase the mechanical strength of fuel assembly from vibration caused by the coolant flow through the subchannels in the fuel assemblies.Therefore, thermal-hydraulics analysis of AP1000 reactor on steady state condition must be carried out to determine the effect of installing the spacer grids in the fuel assemblies. The methodology were making the calculation such as core pressure drops, mass flux and heat transfer coefficient for fuel assemblies without spacer grids and with variation number of spacer grids. The hottest subchannel analysis was focused on the comparative of thermal-hydraulicsof AP1000 reactor on the steady state condition between the hottest subchannel without spacer grids and the hottest subchannel with 8/2 grid nozzle using COBRA-EN code. Compared to the hottest subchannel without spacer grids, the installing 8/2 grid-nozzles on subchannels affected the core pressure drops increased 3.74 times from 73.99 kPa to 276.88 kPa, the coolant mass flux decreased and the heat transfer coefficient fluctuated in the grid spacer region, having an affect on heat transfer process by collant would be more effective. The greater pressure drop would have an affect on increasing the critical heat flux (CHF). Because of the reactor power didn’t change, the heat flux didn’t prone to change, except near the grid spacer region, so the DNBR would increased, its mean that the safety margin would be better. The calculation for the hottest subchannel with 8/2 grid-nozzles compared to the design gave results the core pressure drop was 276.88 kPa (deviation of 0.68%), the coolant outlet temperature was 325.54oC (deviation of 0.21%), the maximum heat flux was 1635.16 kW/m2 (deviation of 0,03%) and the MDNBR was 2.48 (14.06% greater than the W-3 correlation limit). Installing 8/2 grid-nozzles would gave higher safety margin.